La Cour Supreme Et La Reforme Du Code Civil - Jobin, Pierre-Gabriel (The Canadian Bar Review, 2000)
The Supreme Court's influence on the law of the Civil Code ofLower Canada was so determining that it demonstrates that jurisprudence can be a true source of law. In the reform of the Civil Code, not all holdings of the Court were followed by the legislature, but the majority, and the most significant ones were codified. The dark era of the systematic «uniformisation» of Quebec law with the common law is over, nowadays the Court's approach to the civil law is enriched by well-conceived and respectful comparative law. This is yet another reason to regret that so few civil law decisions are handed down by the Court.